Epicrestal and subcrestal placement of platform‐switched implants: 18 month‐result of a randomized, controlled, split‐mouth, prospective clinical trial. Issue 4 (23rd February 2018) - Froum, Stuart J.; Cho, Sang‐Choon; Suzuki, Takanori; Yu, Paul; Corby, Patricia; Khouly, Ismael
Abstract: Objectives: To evaluate the changes in marginal bone levels (MBL) and soft tissue dimension around platform‐switched implants with the implant–abutment junction (IAJ) placed at the crest or 1.5–2 mm subcrestally. Materials and methods: In all, 96 platform‐switched implants were placed in either the posterior maxilla or mandible in 48 partially edentulous patients in a split‐mouth study. All implants were provisionally restored after 4–5 months and definitively after 6 months (T6). Radiographic assessment of MBL was assessed at implant placement (T0), T6, 12 months (T12), and 18 months (T18) after placement. Mid‐buccal soft tissue and papilla measurements were performed at T6, T12, and T18. Results: In all, 43 patients with 86 implants completed the study. The T18 examination showed an implant survival rate of 100% in both groups. Analysis showed that MBL varied as a function of IAJ location, which indicated more coronal bone levels with subcrestal (2.39 ± 0.08 mm) than with epicrestal placements (0.88 ± 0.08 mm) ( p < .05). Greater average marginal bone loss was found in the subcrestal group (0.40 ± 0.07 mm) compared to the epicrestal group (0.13 ± 0.08 mm) although no statistically significant difference was found at T18 ( p > .05). Levels of mid‐buccal soft tissue had no significant changes over time, regardless of group ( p > .05). There was a significant difference in increase in papilla between T6 and T12 and T18 ( p = .005 and .001), but not between T12 and T18 ( p = .61). These papilla levels and changes were similar between groups ( p > .05). Conclusions: The MBL changes around platform‐switched implants with same geometry were not affected by the epicrestal or subcrestal location of the IAJ. Furthermore, the location of the IAJ did not affect the implant survival and soft tissue dimensions. However, no bone loss was located apical to the IAJ when the implants were placed subcrestally.